2013
DOI: 10.1371/journal.pone.0081432
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of PTEN Positive Glioblastoma Stem Cells Identifies DUB3 and Wee1 Modulation in a Cell Differentiation Model

Abstract: The term astrocytoma defines a quite heterogeneous group of neoplastic diseases that collectively represent the most frequent brain tumors in humans. Among them, glioblastoma multiforme represents the most malignant form and its associated prognosis is one of the poorest among tumors of the central nervous system. It has been demonstrated that a small population of tumor cells, isolated from the brain neoplastic tissue, can reproduce the parental tumor when transplanted in immunodeficient mouse. These tumor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…As previously reported, experimental conditions based on culturing freshly dissociated tumor cells in serum-free medium containing EGF and bFGF, allowed the selective growth of cellular clusters resembling tumor spheres (12,17,18,19,21). In the present study, such spheres maintained an undifferentiated state (UPTC), as confirmed by morphological analysis (Fig.…”
Section: Rna-binding Protein Musashi Is Expressed By Uptc Spheres Butsupporting
confidence: 88%
“…As previously reported, experimental conditions based on culturing freshly dissociated tumor cells in serum-free medium containing EGF and bFGF, allowed the selective growth of cellular clusters resembling tumor spheres (12,17,18,19,21). In the present study, such spheres maintained an undifferentiated state (UPTC), as confirmed by morphological analysis (Fig.…”
Section: Rna-binding Protein Musashi Is Expressed By Uptc Spheres Butsupporting
confidence: 88%
“…In a study by Forte et al [ 33 ], SPRY1 was among a number of genes with elevated expression in the undifferentiated glioblastoma-derived neuropsheres as compared to the differentiated glioblastoma-derived primary cultures. An unrelated study Aldaz et al [ 34 ] demonstrated that SPRY1 was over-expressed at the protein level in undifferentiated cells as opposed to cells that had undergone four days of differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Since it is known that PTEN [63] is one of the predicted targets of miR-19a, it is also possible that miR-19a overexpression might be associated with PTEN inactivation inducing cell proliferation in FTC-133, while its inhibition promotes PTEN activation inducing cell growth reduction. In a recent study, Frisk et al have suggested that PTEN suppression is associated in extremely malignant or late-stage thyroid tumors, including ATC [64]. These results suggest that miR-19a leads to the poor prognosis in follicular thyroid cancer cells through stimulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%